Suppression of Adenosine Deaminase and Xanthine Oxidase Activities by Mineralocorticoid and Glucocorticoid Receptor Blockades Restores Renal Antioxidative Barrier in Oral Contraceptive-Treated Dam - Badmus, Olufunto O.; Areola, Emmanuel D.; Benjamin, Eleojo; Obekpa, Matthew A.; Adegoke, Tolulope E.; Elijah, Oluwatobi E.; Imam, Aminu; Olajide, Olayemi J.; Olatunji, Lawrence A. (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Objective. We tested the hypothesis that postpartum combined oral contraceptive (COC) treatment would induce oxidative stress via the adenosine deaminase-xanthine oxidase pathway in the kidney. We also sought to determine whether mineralocorticoid receptor (MR) or glucocorticoid receptor (GR ) blockade would suppress the activities of ADA and xanthine oxidase caused by postpartum COC treatment in the kidney. Methods. Twenty-four Wistar dams were randomly assigned to 4 groups (n=6/group). Dams received vehicle (po), COC (1.0 μg ethinylestradiol and 5.0 μg levonorgestrel; po), COC with GR blockade (mifepristone; 80.0 mg/kg; po), and COC with MR blockade (spironolactone; 0.25 mg/kg; po) daily between 3rd and 11th week postpartum. Results. Data showed that postpartum COC caused increased plasma creatinine and urea, increased renal triglyceride/high-density lipoprotein ratio, free fatty acid accumulation, alanine aminotransferase, gamma-glutamyltransferase, uric acid, and activities of renal XO and ADA. On the other hand, postpartum COC resulted in decreased plasma albumin, renal glutathione, and Na+-K+-ATPase activity with no effect on lactate production. However, MR or GR blockade ameliorated the alterations induced by postpartum COC treatment. The present results demonstrate that MR or GR blockade ameliorates postpartum COC-induced increased activities of ADA and xanthine oxidase and restores glutathione-dependent antioxidative defense. Conclusion. These findings implicate the involvements of GR and MR in renal dysfunctions caused by COC in dams via disrupted glutathione antioxidative barrier.